Ethylene-vinyl acetate copolymer composite material and preparation method thereof
By adopting a new expansion flame retardant system and synergist in EVA materials, the problems of low flame retardant efficiency and poor water resistance in existing EVA materials are solved, and the comprehensive effects of efficient flame retardant, low smoke release and good mechanical properties are achieved.
Patent Information
- Application Number
- CN202411779418.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-11
AI Technical Summary
The existing flame retardant modified EVA materials have low flame retardant efficiency and poor water resistance and smoke resistance, which leads to insufficient strength and density of the carbon layer formed during combustion, and cannot effectively inhibit the release of smoke.
The new expansion flame retardant system is adopted, including piperazine pyrophosphate, expansion carbon-forming agent and gas-phase flame retardant, and the strength and water resistance of the carbon layer are improved by synergistic agents such as polycarbosilane and MQ silicone, thereby enhancing the compatibility of the flame retardant with EVA.
It significantly improves the flame retardant efficiency of EVA materials, reduces flue gas release, enhances water resistance, and maintains good mechanical properties, meeting the high-performance flame retardant needs in the fields of wires, cables, transportation, etc.
Smart Images

Figure BDA0005172412210000061 
Figure BDA0005172412210000062 
Figure BDA0005172412210000071
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer materials, and in particular to an ethylene-vinyl acetate copolymer composite material and a preparation method thereof. Background Art
[0002] Ethylene-vinyl acetate copolymer (EVA) has good flexibility, electrical insulation and chemical stability, and is widely used in wires and cables, transportation, and electronic and electrical fields. However, EVA materials are flammable and are accompanied by a large amount of molten droplets and smoke when burning, which endangers people's lives and property safety. Therefore, it is necessary to modify it to be flame retardant and smoke suppressant to improve the fire safety performance of EVA materials.
[0003] Metal hydroxides have the advantages of being non-toxic, smoke-suppressing, flame-retardant, cheap and readily available. Currently, most flame-retardant modification of EVA uses the addition of metal hydroxides, but there are problems such as large amounts of flame retardants added, and the tensile strength and elongation at break of the material are significantly reduced, which limits their application in some fields. Intumescent flame retardants have higher flame retardant efficiency for EVA and can inhibit droplets during combustion, but existing flame retardants have low flame retardant efficiency. Due to their strong water solubility and polarity, they have poor water resistance. The strength and density of the carbon layer formed during the combustion process are insufficient, causing the carbon layer to crack easily at high temperatures and failing to effectively inhibit the release of smoke. Summary of the invention
[0004] The present invention aims to solve the problems of low flame retardant efficiency, poor water resistance and smoke suppression of the existing flame retardant modified EVA, and provides an ethylene-vinyl acetate copolymer composite material and a preparation method thereof.
[0005] The ethylene-vinyl acetate copolymer composite material of the present invention comprises, by mass percentage, 78-83wt% of ethylene-vinyl acetate copolymer, 16-20wt% of flame retardant, 1-3wt% of synergist, 1-3wt% of compatibilizer, 0.1-1wt% of lubricant and the balance of antioxidant.
[0006] Furthermore, the mass percentage of vinyl acetate in the ethylene-vinyl acetate copolymer is 12% to 24%.
[0007] Furthermore, the flame retardant includes piperazine pyrophosphate, an expanding carbon-forming agent and a gas phase flame retardant; wherein the expanding carbon-forming agent is one or a mixture of any several of melamine polyphosphate, triazine carbon-forming foaming agent, polyphenylene ether, melamine pyrophosphate, dimelamine pyrophosphate, and melamine cyanurate, and the gas phase flame retardant is one or a mixture of two of diethyl aluminum phosphite and aluminum hypophosphite.
[0008] Furthermore, the synergist is one of metal organic framework materials, polycarbosilane, MQ silicone resin, or a mixture of any of them.
[0009] The synergist further comprises one or any combination of silicate, transition metal oxide and hydrotalcite.
[0010] Furthermore, the compatibilizer is one of maleic anhydride grafted polyethylene, silane grafted polyethylene, maleic anhydride grafted EVA, silane grafted EVA, or a mixture of any of them.
[0011] Furthermore, the lubricant is one of polyethylene wax and polypropylene wax, or a mixture of any two of them.
[0012] Furthermore, the antioxidant is one of antioxidant 1010, antioxidant 1035, antioxidant 1076, and antioxidant 168, or a mixture of any of them.
[0013] The preparation method of the ethylene-vinyl acetate copolymer composite material of the present invention comprises the following steps:
[0014] 1. First, add the flame retardant, synergist, compatibilizer, lubricant and antioxidant into a high-speed mixer and mix them evenly, then add ethylene-vinyl acetate copolymer and continue to mix evenly to obtain a mixed material;
[0015] 2. Then the mixed material is added into an internal mixer, melt blended by heating, and compression molded to prepare an ethylene-vinyl acetate copolymer composite material.
[0016] Furthermore, the heating temperature of the internal mixer is 160-180° C., and the rotation speed of the rotor is 30-45 r / min.
[0017] Beneficial effects of the present invention:
[0018] The invention departs from the expansion flame retardant system with ammonium polyphosphate as the core component and adopts a brand-new expansion flame retardant system. Piperazine pyrophosphate has excellent charring performance and works together with the expansion agent and the gas phase flame retardant to improve the flame retardant efficiency of EVA.
[0019] The polycarbosilane in the synergist used in the present invention is a ceramic precursor, which can effectively improve the strength of the carbon layer and the thermal stability at high temperature. The polycarbosilane with a low degree of polymerization can be melted during material processing and easily dispersed evenly in the material. Its hydrophobicity allows it to migrate to the surface of the material during material processing and pressing, thereby improving the water resistance of the material. By modifying the surface of the flame retardant with an organic metal framework material, the compatibility of the flame retardant and EVA is improved, and the flame retardant efficiency and smoke suppression performance of the material are improved. When MQ silicone resin burns, nano-silicon dioxide is formed, which improves the strength of the carbon layer. At the same time, its low surface energy property allows it to migrate to the surface of the material, thereby improving the water resistance of the material.
[0020] The present invention prepares an EVA composite material with high efficiency flame retardancy, low smoke release, water resistance and good mechanical properties, which meets the needs of different fields such as wires and cables, transportation and the like for high-performance flame retardant EVA composite materials. DETAILED DESCRIPTION
[0021] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any combination of the specific implementation modes.
[0022] Specific implementation method 1: The ethylene-vinyl acetate copolymer composite material of this implementation method includes, by mass percentage, 78-83wt% of ethylene-vinyl acetate copolymer, 16-20wt% of flame retardant, 1-3wt% of synergist, 1-3wt% of compatibilizer, 0.1-1wt% of lubricant and the remainder of antioxidant.
[0023] Specific implementation method 2: In this implementation method, the mass percentage of vinyl acetate in the ethylene-vinyl acetate copolymer is 12% to 24%. Other steps and parameters are the same as those in the specific implementation method 1.
[0024] Specific implementation method three: The flame retardant in this implementation method includes piperazine pyrophosphate, an expanded carbon-forming agent and a gas phase flame retardant; wherein the expanded carbon-forming agent is one or a mixture of any of melamine polyphosphate, triazine carbon-forming foaming agent, polyphenylene ether, melamine pyrophosphate, dimelamine pyrophosphate, and melamine cyanurate, and the gas phase flame retardant is one or a mixture of two of diethyl aluminum phosphinate and aluminum hypophosphite. Other steps and parameters are the same as those in specific implementation method one or two.
[0025] Among the flame retardants, piperazine pyrophosphate has excellent charring properties, melamine polyphosphate and dimelamine pyrophosphate have excellent expansion properties, triazine charring foaming agent has both charring and expansion properties, aluminum diethylphosphinate and aluminum hypophosphite mainly play a gas phase flame retardant role, and play a multi-phase synergistic flame retardant of the condensed phase and the gas phase in the expansion flame retardant system, thereby improving the flame retardant efficiency of EVA.
[0026] Specific embodiment 4: In this embodiment, the synergist is one of metal organic framework materials, polycarbosilane, MQ silicone resin or a mixture of any of them. Other steps and parameters are the same as those of specific embodiments 1 to 3.
[0027] Specific implementation mode 5: In this implementation mode, the synergist further comprises one or any combination of silicate, transition metal oxide and hydrotalcite. Other steps and parameters are the same as those of specific implementation mode 4-1.
[0028] Polycarbosilane is a ceramic precursor that can effectively improve the strength of the carbon layer and its thermal stability at high temperatures. Polycarbosilane with a low degree of polymerization can melt during material processing and is easily dispersed evenly in the material. Its hydrophobic properties allow it to migrate to the surface of the material during material processing and pressing, thereby improving the material's water resistance. MQ silicone resin forms nano-silicon dioxide when it burns, which improves the strength of the carbon layer. At the same time, its low surface energy allows it to migrate to the surface of the material, thereby improving the material's water resistance.
[0029] Metal-organic framework materials are organic-inorganic hybrid materials with high specific surface areas. After being coated on the surface of the flame retardant, they promote the compatibility of the flame retardant with the EVA matrix, inhibit the migration of the flame retardant, and reduce the effect of the flame retardant modification on the mechanical properties of the material. The metal-organic framework material has good dispersibility in EVA and produces nano-metal oxides during combustion. It has a higher specific surface area and can effectively catalyze the flame retardant material into carbon. At the same time, the metal ions can complex with the acid produced by the decomposition of the flame retardant, leaving more flame retardants in the condensed phase and forming a higher quality carbon layer, thereby improving the flame retardancy and smoke suppression properties of the material.
[0030] Metal oxides, silicates, and hydrotalcites can effectively catalyze flame retardants into carbon during the combustion process, forming a richer carbon layer while strengthening the strength of the carbon layer, inhibiting the release of combustibles and smoke, and retaining more combustibles in the condensed phase, thereby reducing the combustion intensity of the material and the release of smoke.
[0031] Specific implementation example 6: In this implementation example, the compatibilizer is one or a mixture of maleic anhydride grafted polyethylene, silane grafted polyethylene, maleic anhydride grafted EVA, silane grafted EVA. Other steps and parameters are the same as those in specific implementation examples 1 to 5.
[0032] The compatibilizer in this embodiment is used to improve the compatibility of the filler and the matrix so as to reduce the influence on the mechanical properties of the EVA composite material.
[0033] Specific implementation method 7: In this implementation method, the lubricant is polyethylene wax, polypropylene wax, or a mixture of any two of them. Other steps and parameters are the same as those of specific implementation methods 1 to 6.
[0034] The lubricant in this embodiment is used to improve the surface gloss and processing performance of the material.
[0035] Specific embodiment eight: In this embodiment, the antioxidant is one of antioxidant 1010, antioxidant 1035, antioxidant 1076, and antioxidant 168, or a mixture of any of them. Other steps and parameters are the same as those of specific embodiments one to seven.
[0036] Ethylene-vinyl acetate copolymer is prone to aging and degradation during high-temperature melt processing and use. At the same time, flame retardant modification often accelerates the aging of the material, and the aged material is more flammable. Therefore, antioxidants are added to give the material lasting flame retardant properties and extend its safe service life.
[0037] Specific embodiment 9: The preparation method of the ethylene-vinyl acetate copolymer composite material of this embodiment comprises the following steps:
[0038] 1. First, add the flame retardant, synergist, compatibilizer, lubricant and antioxidant into a high-speed mixer and mix them evenly, then add ethylene-vinyl acetate copolymer and continue to mix evenly to obtain a mixed material;
[0039] 2. Then the mixed material is added into an internal mixer, melt blended by heating, and compression molded to prepare an ethylene-vinyl acetate copolymer composite material.
[0040] Specific embodiment 10: The heating temperature of the internal mixer in this embodiment is 160-180° C., and the rotating speed of the rotor is 30-45 r / min. Other steps and parameters are the same as those in specific embodiment 9.
[0041] The embodiments of the present invention are described in detail below. The following embodiments are implemented on the premise of the technical solution of the present invention, and detailed implementation schemes and specific operation processes are given, but the protection scope of the present invention is not limited to the following embodiments.
[0042] Embodiment 1:
[0043] The preparation method of the ethylene-vinyl acetate copolymer composite material of this embodiment comprises the following steps:
[0044] 12wt% of piperazine pyrophosphate, 4wt% of aluminum diethylphosphinate, 1wt% of polyphenylene oxide, 1wt% of polycarbosilane, 1wt% of maleic anhydride grafted EVA, 0.6wt% of polyethylene wax and 0.4wt% of antioxidant 1010 are mixed in a high-speed mixer for 5 minutes, and then 80wt% of ethylene-vinyl acetate copolymer is added and mixed evenly to obtain a mixed material. The mixed material is added to an internal mixer, heated and melted, and put into a mold and pressed by a flat vulcanizer to prepare an ethylene-vinyl acetate copolymer composite material.
[0045] The heating temperature of the internal mixer is 160°C and the rotating speed of the rotor is 30r / min.
[0046] Embodiment 2:
[0047] The preparation method of the ethylene-vinyl acetate copolymer composite material of this embodiment comprises the following steps:
[0048] 13wt% of piperazine pyrophosphate, 2wt% of melamine cyanurate, 1wt% of aluminum hypophosphite, 1wt% of cerium-based metal organic framework (Ce-MOF), 1.0wt% of maleic anhydride grafted EVA, 0.5wt% of polyethylene wax and 0.5wt% of antioxidant 1010 were mixed in a high-speed mixer for 5 minutes, and then 81wt% of ethylene-vinyl acetate copolymer was added and continued to mix evenly to obtain a mixed material. The mixed material was added to an internal mixer, heated and melted, and put into a mold and pressed by a flat vulcanizer to prepare an ethylene-vinyl acetate copolymer composite material.
[0049] The heating temperature of the internal mixer is 160°C and the rotating speed of the rotor is 30r / min.
[0050] Embodiment 3:
[0051] The preparation method of the ethylene-vinyl acetate copolymer composite material of this embodiment comprises the following steps:
[0052] 10wt% of piperazine pyrophosphate, 4wt% of triazine carbon-forming foaming agent, 2wt% of dimelamine pyrophosphate, 1.0wt% of silane-grafted EVA, 1wt% of MQ silicone resin, 0.5wt% of polypropylene wax and 0.5wt% of antioxidant 1035 are mixed in a high-speed mixer for 5 minutes, and then 81wt% of ethylene-vinyl acetate copolymer is added and mixed evenly to obtain a mixed material. The mixed material is added to an internal mixer, heated and melted, and put into a mold and pressed and formed by a flat vulcanizer to prepare an ethylene-vinyl acetate copolymer composite material.
[0053] The heating temperature of the internal mixer is 160°C and the rotating speed of the rotor is 30r / min.
[0054] Embodiment 4:
[0055] The preparation method of the ethylene-vinyl acetate copolymer composite material of this embodiment comprises the following steps:
[0056] 13wt% of piperazine pyrophosphate, 3wt% of melamine polyphosphate, 1wt% of polyphenylene ether, 1.0wt% of silane-grafted EVA, 0.7wt% of nickel-based metal organic framework material (MOF-74), 0.3wt% of organic montmorillonite, 0.5wt% of polypropylene wax and 0.5wt% of antioxidant 1035 were mixed in a high-speed mixer for 5 minutes, and then 80wt% of ethylene-vinyl acetate copolymer was added and continued to mix until uniform. The materials were added to an internal mixer, heated and melted, and put into a mold and pressed by a flat vulcanizer to prepare an ethylene-vinyl acetate copolymer composite material.
[0057] The heating temperature of the internal mixer is 160°C and the rotating speed of the rotor is 30r / min.
[0058] The performance test of the ethylene-vinyl acetate copolymer composite material prepared in the above example is as follows:
[0059] (1) According to ASTM D3801, the vertical burning rating of polyethylene materials was tested using a CZF-2 instrument (China Jiangning Analytical Instrument Co., Ltd.). The sample size was 130 mm × 13 mm × 3.2 mm.
[0060] (2) According to ASTM D2863, the limiting oxygen index of polyethylene was tested using a JF-3 instrument (Jiangning Analytical Instrument Co., Ltd., China). The sample size was 130 mm × 6.5 mm × 3 mm.
[0061] The test results are shown in Table 1: the flame retardant modified ethylene-vinyl acetate copolymer (EVA) composite materials can pass the UL-94V-0 level in the vertical combustion test, and the limiting oxygen index (LOI) value exceeds 27.0%, indicating that the intumescent flame retardant system of the present invention has excellent flame retardant efficiency for ethylene-vinyl acetate copolymer.
[0062] Table 1 Vertical combustion (UL-94) and limiting oxygen index (LOI) test results of EVA materials
[0063]
[0064] (3) According to ISO-5660 standard, ethylene-vinyl acetate copolymer material was tested by cone calorimetry test. The test results of heat release rate (HRR), total heat release (THR), smoke release rate (SPR) and total smoke release (TSP) are shown in Table 2. The sample size is 100 mm × 100 mm × 4 mm, and the thermal radiation intensity is 50 kW / m 2 .
[0065] Table 2 Cone calorimetry test data of EVA materials
[0066]
[0067] Under a thermal radiation intensity of 50 kW, pure ethylene-vinyl acetate copolymer continues to burn after ignition until it is completely burned out. It has no carbon-forming properties. The peak heat release rate (pHRR) and peak smoke release rate (pSPR) are 1935.1 kW / m 2 and 0.087m 2 / s, the total heat release (THR) and total smoke release (TSP) reached 261.1MJ / m 2and 16.1m 2 .
[0068] The flame retardant modified ethylene-vinyl acetate copolymer material has significantly reduced combustion parameters compared to the unmodified material. Among them, Ce-MOF has excellent synergistic flame retardant effect in the intumescent flame retardant system, effectively inhibiting the release of smoke and heat.
[0069] (4) According to GB / T528-2009 standard, the mechanical properties of ethylene-vinyl acetate copolymer materials were tested by a universal mechanical testing machine. The sample to be tested was dumbbell-shaped and the tensile speed was 200 mm min. -1 The test results are shown in Table 3. The ethylene-vinyl acetate copolymer composite materials prepared in the above examples all maintain excellent mechanical properties.
[0070] Table 3 Mechanical properties test results of EVA materials
[0071]
[0072] (5) Water resistance test
[0073] In order to evaluate the water resistance of the ethylene-vinyl acetate copolymer composite material prepared above, the initial mass is recorded as m 0 Then place the sample in a closed constant temperature water bath for 168 hours at 70°C, and replace the distilled water every 24 hours. After the test, remove the moisture on the surface of the sample with filter paper and weigh the mass, which is recorded as m. 1 The sample was dried in an oven at 105°C until constant weight was recorded as m 2 .
[0074] Water absorption rate (%) = (m 1 -m 0 ) / m 0 ×100%(Formula 1)
[0075] Mass loss rate (%) = (m 2 -m 1 ) / m 1 ×100%(Formula 2)
[0076] The water absorption rate and mass loss rate were obtained according to the above formula. The samples after water resistance test and drying were tested respectively, and the test results are shown in Table 4.
[0077] It can be seen from Table 4 that the mechanical and flame retardant properties of the ethylene-vinyl acetate copolymer composite material are maintained well after the water resistance test for 168 h, indicating that the prepared ethylene-vinyl acetate copolymer composite material has excellent water resistance.
[0078] Table 4 Results of EVA composite water resistance test
[0079]
Claims
1. An ethylene-vinyl acetate copolymer composite material, characterized in that: The composite material comprises, by mass percentage, 78-83wt% of ethylene-vinyl acetate copolymer, 16-20wt% of flame retardant, 1-3wt% of synergist, 1-3wt% of compatibilizer, 0.1-1wt% of lubricant and the balance of antioxidant.
2. The ethylene-vinyl acetate copolymer composite material according to claim 1, characterized in that: The mass percentage of vinyl acetate in the ethylene-vinyl acetate copolymer is 12% to 24%.
3. An ethylene-vinyl acetate copolymer composite material according to claim 1 or 2, characterized in that: The flame retardant includes piperazine pyrophosphate, an expanding carbon-forming agent and a gas phase flame retardant; wherein the expanding carbon-forming agent is one or a mixture of any of melamine polyphosphate, triazine carbon-forming foaming agent, polyphenylene ether, melamine pyrophosphate, dimelamine pyrophosphate, and melamine cyanurate, and the gas phase flame retardant is one or a mixture of two of diethyl aluminum phosphite and aluminum hypophosphite.
4. The ethylene-vinyl acetate copolymer composite material according to claim 1, characterized in that: The synergist is one of metal organic framework materials, polycarbosilane, and MQ silicone resin, or a mixture of any of them.
5. The ethylene-vinyl acetate copolymer composite material according to claim 1, characterized in that: The synergist further comprises one or any combination of silicate, transition metal oxide and hydrotalcite.
6. The ethylene-vinyl acetate copolymer composite material according to claim 5, characterized in that: The compatibilizer is one of maleic anhydride grafted polyethylene, silane grafted polyethylene, maleic anhydride grafted EVA, silane grafted EVA or a mixture of any of them.
7. The ethylene-vinyl acetate copolymer composite material according to claim 1, characterized in that: The lubricant is one of polyethylene wax and polypropylene wax or a mixture of any two of them.
8. The ethylene-vinyl acetate copolymer composite material according to claim 1, characterized in that: The antioxidant is one of antioxidant 1010, antioxidant 1035, antioxidant 1076, and antioxidant 168, or a mixture of any of them.
9. The method for preparing the ethylene-vinyl acetate copolymer composite material according to claim 1, characterized in that: The method comprises the following steps:
1. First, add the flame retardant, synergist, compatibilizer, lubricant and antioxidant into a high-speed mixer and mix them evenly, then add ethylene-vinyl acetate copolymer and continue to mix evenly to obtain a mixed material; 2. Then the mixed material is added into an internal mixer, melt blended by heating, and compression molded to prepare an ethylene-vinyl acetate copolymer composite material.
10. The method for preparing the ethylene-vinyl acetate copolymer composite material according to claim 9, characterized in that: The heating temperature of the internal mixer is 160-180°C, and the rotation speed of the rotor is 30-45r / min.
Citation Information
Patent Citations
Hydrolysis-resistant migration-free halogen-free flame-retardant polyolefin composition and preparation method thereof
CN104059278A
Halogen-free flame retardant polyether thermoplastic polyurethane elastomer and preparation method thereof
CN104693782A
Flame retardant and soundproof composite material for rail transit and preparation method thereof
CN109251403A
High-expansion fireproof low-smoke halogen-free flame retardant composition and thermoplastic resin composition
CN113583299A
High-gloss low-precipitation flame-retardant polypropylene composition as well as preparation method and application thereof
CN114213761A